Pipeline Embolization Device for Salvage Treatment of a Willis Covered Stent Prolapse Into the Aneurysmal Sac - Wu, Zeng-Bao; Wang, Sheng; Song, Li-Gang; Yang, Xin-Jian; Mu, Shi-Qing (Frontiers in Neurology, 2019)
The Willis covered stent (WCS) can sometimes prolapse into the aneurysmal sac in an unexpected manner during or shortly after its deployment due to device migration. In this report, we describe a useful salvage strategy, which can be used to reposition a prolapse WCS construct into a more favorable alignment. In a 70-year-old woman had an intra-procedural prolapse of a WCS into a large cavernous aneurysm, a Pipeline embolization device (PED) was used to adjust the prolapse, reorient the WCS construct, and achieve successful flow diversion. Maintaining proximal access and making sure the wire has safely remained within the central axis of the stent are critical until the entire parent vessel is reconstructed. The salvage technique described may help regain proximal access and reposition the flow diversion constructs when encountering this potential complication.